Pengaruh Serat Kulit Kayu Gelam Terhadap Kuat Tarik Lentur Beton Menggunakan Semen OPC - Awan, Herdi; DWSBU, Caterina Niken; Putra, Sasana (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2020)
The load from vehicles received by rigid pavement is characterized as dynamic load that move and change quantitively, so the r2eaction accepted by rigid pavement is the combination of compressive and tensile strength. In the reaserch, as the effort to know the effect of flexural and split tensile strength on normal quality concrete with 0%, 0,4%, 0,6% and 0,8%. The samples of flexural tensile strength testimonial use 60 cm x 15cm x 15 cm beam and the sampes of split tensile and compressive strength test use 15 cm x 30 cm cylinder. As the result, the concrete sample with 0,4% of volume fraction has the most significant progress in the flexural tensile strength, split tensile strength and compressive strength. The result of this research also shows that the progress of flexural tensile test sample reach 9,42%, split tensile strength 7,5% and compressive strength 6,12% from concrete sample with 0% of volume fraction and it has decreased test result from 0,6% and 0,8% of volume fraction. The maximum of flexural tensile test, split tensile test, and compressive test are 6,62 MPa, 2,58 MPa, and 30,54 MPa. Key words : Melaleuca bark fiber, flexural tensil strength,split tensil strength, compressive strength, volume fraction, and rigid pavement.